Crisis management according to the strategic leadership - the interactive role of decision support systems. (An exploratory study at the Ministry of Industry and Minerals / the State Company for Steel Industries) - Hussein, Sajid Nasser; Ali, Sheffaa Mohammed (Journal of Economics and Administrative Sciences, 2021)
The researcher aims to Diagnose the reality of research variables, strategic leadership and decision support systems, and their impact on crisis management in the General Company for Steel Industries because of their important role in preventing crises and reducing their occurrence for the research company in particular and other companies in general affiliated with the Ministry of Industry and Minerals, as well as clarifying theoretical concepts of research variables As it included the answer to questions related to the research problem, including (Is there an impact of the strategic leadership in managing crises if decision support systems are used), and the researcher adopted the descriptive and analytical approach in its completion and the questionnaire as a tool in collecting data and information related to the research, and it was distributed to an intended sample consisting of (125) employees so that the number of final forms valid for analysis is (112) respondents. The research yielded a number of conclusions, perhaps the most prominent of which is the validity of the combined effect of strategic leadership and decision support systems in crisis management, as well as the lack of an interactive relationship between strategic leadership and decision support systems and their impact on crisis management. The research also included a number of recommendations, the most important of which is the need for senior management in the General Company for Steel Industries to increase interest and achieve communication for both interacting variables, strategic leadership and decision support systems, and to effectively invest the interactive relationship, especially when defining the strategic direction that affected the formation of the interactive relationship between them with crisis